2007
DOI: 10.1111/j.1365-3156.2007.01841.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Schistosoma mansoni and hookworm in urban farming communities in western Côte d'Ivoire

Abstract: Summaryobjectives To identify risk factors for Schistosoma mansoni and hookworm infections in urban farming communities, and to investigate small-scale spatial patterns of infection prevalence.methods A cross-sectional survey was carried out in 113 farming households (586 individuals) and 21 non-farming households (130 individuals) from six agricultural zones in the town of Man, western Cô te d'Ivoire. Heads of households were interviewed on common agricultural activities, land and water use, education attainm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
74
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 51 publications
(64 reference statements)
18
74
0
1
Order By: Relevance
“…The fi ndings of the current study also showed that participants aged 20 -40 years were signifi cantly more prone to be infected than younger and older ones. This result was in agreement with previous reports worldwide ( Raja'a et al, 2000;Gryseels et al, 2006;Mafuyai et al, 2006;Matthys et al, 2007;Ugbomoiko et al, 2010;Deribe et al, 2011). This could be explained by the excessive mobility of people at this age and they may become more exposed to infected water while swimming/playing or fetching water for domestic purposes or helping in agriculture activities.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The fi ndings of the current study also showed that participants aged 20 -40 years were signifi cantly more prone to be infected than younger and older ones. This result was in agreement with previous reports worldwide ( Raja'a et al, 2000;Gryseels et al, 2006;Mafuyai et al, 2006;Matthys et al, 2007;Ugbomoiko et al, 2010;Deribe et al, 2011). This could be explained by the excessive mobility of people at this age and they may become more exposed to infected water while swimming/playing or fetching water for domestic purposes or helping in agriculture activities.…”
Section: Discussionsupporting
confidence: 83%
“…These are consistent with many other reports worldwide (Garba et al, 2010;Ahmed et al, 2012). Males usually have higher prevalence rates of schistosomiasis than females and this was attributed to religious and cultural reasons or to water contact behavior (El-Khoby et al, 2000;Haidar, 2001;Matthys et al, 2007;Deribe et al, 2011). However, signifi cantly higher infection rates among females compared to their male counterparts have been also reported elsewhere (Satayathum et al, 2006;Rudge et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Indeed, while in some schools no child was infected with S. mansoni, more than half of the children were infected in other schools. High prevalences of S. mansoni were mostly found in the northern Tonkpi region, which is in line with results from previous studies (Roux et al, 1980;Utzinger et al, 2000;Keiser et al, 2002;Matthys et al, 2007). In the schools located in the Cavally and Gomon regions, S. mansoni infection prevalences mainly ranged between 10 and 45%.…”
Section: Discussionsupporting
confidence: 81%
“…A similar study by Bogoch et al [23] in the northern region of Ghana also identified working or playing near freshwater bodies as having a significant association with S. haematobium infection. Such association between proximity of home or school to schistosome infested water sources and infection has been reported from many other studies in schistosomiasis endemic communities including Ethiopia [6,24], Sudan [25], Côte d'Ivoire [26] and Yemen [16,27].…”
Section: Discussionmentioning
confidence: 95%